2016
DOI: 10.1167/16.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Salient in space, salient in time: Fixation probability predicts fixation duration during natural scene viewing

Abstract: During natural scene viewing, humans typically attend and fixate selected locations for about 200-400 ms. Two variables characterize such "overt" attention: the probability of a location being fixated, and the fixation's duration. Both variables have been widely researched, but little is known about their relation. We use a two-step approach to investigate the relation between fixation probability and duration. In the first step, we use a large corpus of fixation data. We demonstrate that fixation probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…Incorporating fixation durations in the analysis would make it possible to assess interactions between fixation locations and durations. In a recent study, Einhäuser and Nuthmann () showed that fixation durations on semantically relevant parts of scenes are longer than fixation durations on other parts, in line with our finding that infant fixation durations were longer in regions more frequently fixated by adults. When locations are fixated may be an important factor to study as well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Incorporating fixation durations in the analysis would make it possible to assess interactions between fixation locations and durations. In a recent study, Einhäuser and Nuthmann () showed that fixation durations on semantically relevant parts of scenes are longer than fixation durations on other parts, in line with our finding that infant fixation durations were longer in regions more frequently fixated by adults. When locations are fixated may be an important factor to study as well.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of attention allocation addresses the where , and the fixation duration analysis addresses the when . This distinction is typical in the scene perception literature, as there are studies examining fixation locations or durations, but almost never both; exceptions are papers by Tatler, Brockmole, and Carpenter () and Einhäuser and Nuthmann (). Since the saliency model of Itti and Koch (), many newer saliency models have been proposed (for a review see, Borji et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be quantified by empirical saliency, usually measured by the density maps of fixations over multiple observers. It has been recently shown that locations with higher saliency have higher fixation durations (Einhäuser & Nuthmann, 2016). Given our findings and what has been found about the interaction of saliency and fixation durations, we predicted prolonged fixation durations if an image has multiple distinct peaks of empirical salience against other locations without these distinct peaks.…”
Section: Evidence Accumulation With Multiple Targetssupporting
confidence: 69%
“…In simple reaction-time experiments, Drazin (1961) observed an exponential decay when the foreperiod, the period between warning signal and go signal, was increased. This mimics our forced fixation effect and could be an alternative explanation.…”
Section: Exploration-exploitationmentioning
confidence: 99%
“…By establishing such template fixation maps for scene encoding, we were able to quantify the deployment of visual attention on a trialby-trial basis, allowing us to implement trial-level generalized linear mixed-effect models (GLMMs) that can isolate effects of viewing tasks, fixation counts, and visual attention, respectively. This procedure mimics analyses from recent eye-tracking studies, which used linear mixed-effect model analyses to study task effects on fixation durations (Einhäuser & Nuthmann, 2016;Nuthmann, 2017) and object memory (Draschkow & Võ, 2016;Josephs et al, 2016;. We also examined the relationship between scene memory and scene aesthetic preference by collecting scene preference ratings from a group of participants that were recruited online, called G3, because scene aesthetics are known to be significantly associated with scene memorability (Isola, Xiao, Parikh, Torralba, & Oliva, 2014).…”
Section: Introductionmentioning
confidence: 99%